Formations of the body: Talal Asad and the secular - Peksöz, Ömer Faruk. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
The present study aspires to read Talal Asad’s Genealogies of Religion and Formations of the Secular not as works of anthropology of religion, but as one major contribution to body studies. The novelty of this thesis lies in its argument that Asad’s reflections on the religious and the secular in two separate works comprise in fact one theory of the body. Asad’s critique of the concepts of the secular and the religion is the ground upon which his theory of the body is constructed. His genealogy of the attitudes towards the body via the changing juridical practices in the European Middle Ages is Asad’s treatment of bodily pain in the economy of truth. Asad’s theory of the body is complemented with the examination of modern conceptions of agency, pain, and cruelty with regards to the concept of the secular and secularism. Accompanying this reading of Asad, this study is to maintain that “the religious” and “the secular” as opposites are but the products of modern thinking; that “the secular” precedes “secularism”; and, most importantly, that Asad deconstructs the binary opposition of “the religious” and “the secular” within the horizon of the body. Reading the shifts in the attitudes towards and understandings of the body especially in the history of Christianity, Asad develops a theory of the body. I attempt in this thesis as a consequence to introduce body studies to Talal Asad’s theory of the body.
Keywords: Secularization -- Eastern Hemisphere .